INFLUENCE OF EDUCATORS’ PERCEPTION OF GEN Z STUDENTS IN HIGHER EDUCATION - Cickovska, Elena (Horizons - International Scientific Journal, 2022)
The article aims to reveal the relationship between educators’ misperception of Gen Z students as a generation, educators’ attitude, instructional behavior, students learning engagement and performance. Presented are the results of two complementary qualitative studies conducted at the same higher education institution with educators (N 35) and students (N 184) in 2020 and 2022. Both groups report inadequacy and dissatisfaction in the others behavior,in the teaching process and communication. Referenced with findings from other research the results indicate that students’ unrecognized generational characteristics and preferences lead to a reciprocal adverse influence on educational engagement of both, students and professors, andthus affects the learning outcomes. In order to break the vicious circle, educators need to familiarize with the characteristics of the students’ generation and need guidance to optimize communication and implement a student-centered teaching approach.